Rethinking human-animal relations: The critical role of social psychology. (September 2019) - Dhont, Kristof; Hodson, Gordon; Loughnan, Steve; Amiot, Catherine E.
People deeply value their social bonds with companion animals, yet routinely devalue other animals, considering them mere commodities to satisfy human interests and desires. Despite the inherently social and intergroup nature of these complexities, social psychology is long overdue in integrating human-animal relations in its theoretical frameworks. The present body of work brings together social psychological research advancing our understanding of: 1) the factors shaping our perceptions and thinking about animals as social groups, 2) the complexities involved in valuing (caring) and devaluing (exploiting) animals, and 3) the implications and importance of human-animal relations for human intergroup relations. In this article, we survey the diversity of research paradigms and theoretical frameworks developed within the intergroup relations literature that are relevant, perchance critical, to the study of human-animal relations. Furthermore, we highlight how understanding and rethinking human-animal relations will eventually lead to a more comprehensive understanding of many human intergroup phenomena.